Beyond Border Binaries: Borderlines, Borderlands, and In-Betweenness in Thomas King’s Short Story “Borders” - Mayer, Evelyn (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2011)
The concerns at the border in the late twentieth and early twenty-first centuries are not so much goods and customs any longer but establishing the identity and citizenship of those crossing the line. This focus increased further after 9/11 with new security concerns and the ensuing thickening of the Canada–US border. With the mother, one of the protagonists in Thomas King’s short story “Borders,” insisting on her Blackfoot identity, she and her son are stuck in the middle. They can neither go back to Canada nor cross the border into the United States. Quite literally, they are stranded in what Homi K. Bhabha called “third space.” The setting of the duty-free store, located “between the two borders” (King 134), thus acquires a new meaning as a place of refuge, hybridity, and third space beyond border binaries.